Efektifitas Program Bantuan Sosial Pada Panti Asuhan Kartini Kabupaten Merauke - Oja, Hubertus; Kontu, Francin; Aimok, Godefridus (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2023)
The purpose of this study was to determine the effectiveness of social assistance programs by the Social Service in providing social assistance to orphanages in Merauke. The research method uses a qualitative approach. To obtain this research data, researchers interviewed 14 informants who were designated as research informants. Data analysis using qualitative methods, a discriptive approach. The author's data analysis technique uses three stages, namely, data reduction, data presentation, and conclusions. The results of this study researchers that the effectiveness of social assistance from the Social Service to the Kartini Merauke orphanage has been effective but not maximized because the assistance provided is adjusted to the existing budget related to the social assistance budget. This is in accordance with the measure of effectiveness of social assistance programs, one of which is related to income, namely the government must set a minimum income limit for each citizen in order to meet their daily needs. The adaptability or flexibility of the aid provider has not adjusted to the needs of the target group as a beneficiary. Therefore, there is a need for external involvement to take part in social assistance programs.